Evaluation of the Properties and Compositions of Blended Bio-jet Fuels Derived from Fast Pyrolysis Bio-oil made from Wood According to Aging Test - Jeon, Hwayeon; Youn, Jumin; Park, Jo Yong; Yim, Eui-Soon; Ha, Jeong-Myeong; Park, Young-Kwon; Lee, Jae Woo; Kim, Jae-Kon (The Korean journal of chemical engineering, 2024)
The aviation industry has set ambitious goals for reducing carbon emissions, with the International Civil Aviation Organization targeting net-zero carbon emissions by 2050. Bio-jet fuel is expected to play a crucial role in achieving this target, and the demand for bio-jet fuel is projected to rapidly increase. Bio-oil from fast pyrolysis of lignin, such as waste wood, is considered a promising alternative for production of bio-jet fuel through processes such as hydrodeoxygenation. In this study, the physical properties and compositions of bio-jet fuel produced from wood-derived pyrolysis bio-oil blended with petroleum-based jet fuel as well as their changes during 16 weeks storage were investigated. Consistently, 0%, 10%, 50%, and 100% blended bio-jet fuels were prepared. After 16 weeks of aging, the total acid number of the all-blended bio-jet fuel showed a sharp increase from 12 weeks, reaching over 0.1 mg KOH/g. Additionally, kinematic viscosity showed a steady increase over 16 weeks whereas oxidative stability decreased by approximately 20% at 16 weeks for the 100% bio-jet fuel alone. The final boiling point increased by up to 20% in higher blends of bio-jet fuel and the average molecular weight increased. Bio-jet fuel has a high olefin content, which can further increase during storage, leading to a decrease in the combustion characteristics. This study suggests that using up to 10% the bio-jet fuel in aircraft is safe considering storage stability, but further research is required to confirm this finding.